A multiyear dynamic approach for transmission expansion planning and long-term marginal costs computation - João Tomé Saraiva (2005)
This paper presents a multicriteria formulation for multiyear dynamic transmission expansion planning problems. This formulation considers three criteria: investment costs, operation costs and the expected energy not supplied. The solution algorithm adopts an interactive decision making approach that starts at a non-dominated solution of the problem. This solution is identified transforming two of the three criteria in constraints specifying aspiration levels, and using afterwards Simulated Annealing to deal with the integer nature of investment decisions. After obtaining this first solution, the decision maker can alter the aspiration levels and run the application again to obtain a new solution. Once an expansion plan is accepted, the algorithm computes long-term marginal costs, reflecting both investment and operation costs. These costs are more stable than short term ones and inherently address the Revenue Reconciliation Problem well known in short term approaches. The developed algorithm is tested using a case study based on the Portuguese 400/220/150 kV transmission network.